2010
DOI: 10.1007/s00402-010-1167-3
|View full text |Cite
|
Sign up to set email alerts
|

Infiltration of plasma rich in growth factors for osteoarthritis of the knee short-term effects on function and quality of life

Abstract: At 6 months following intra-articular infiltration of PRGF in patients with OA of the knee, improvements in function and quality of life were documented by OA-specific and general clinical assessment instruments. These favourable findings point to consider PRGF as a therapy for OA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
131
1
9

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(157 citation statements)
references
References 24 publications
16
131
1
9
Order By: Relevance
“…13,[24][25][26][27][28] Although these studies may provide evidence in regard to the safety of the PRP procedure, due to the lack of comparator, they cannot give an insight into the effectiveness of the procedure. The largest case series described the results of 261 patients injected three times with PRP at 2-week intervals.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…13,[24][25][26][27][28] Although these studies may provide evidence in regard to the safety of the PRP procedure, due to the lack of comparator, they cannot give an insight into the effectiveness of the procedure. The largest case series described the results of 261 patients injected three times with PRP at 2-week intervals.…”
Section: Resultsmentioning
confidence: 99%
“…At 6-month follow-up, clinically significant improvements in arthritis scores, quality of life (SF-36), and functional scores were reported when compared with baseline values, with no adverse events described. 28 The case series with the longest follow-up period reported on 91 patients who received three injections of PRP given at 3-weekly intervals. A decrease in pain and an increase in function scores were reported after 12 months when compared with baseline.…”
Section: Resultsmentioning
confidence: 99%
“…15 Wang Saegusa et al reported improvement of VAS, SF-36, and Western Ontario and McMaster Universities (WOMAC) scores at the 6-month follow-up in 261 patients with OA symptoms more than 3 months who had 3 intra-articular injection of autologous PRGF at 2-week intervals. 16 Filardo et al reported that 3 injections of intra-articular PRP in 90 patients with chronic knee degenerative conditions revealed improvement in International Knee Documentation Committee (IKDC) and EQ-VAS scores at the 2-year follow-up and that it had discernible positive effects especially on younger patients with early osteoarthritis. 17 However which growth factors are more beneficial needs better understanding.…”
Section: Discussionmentioning
confidence: 99%
“…2 No major complications were noted in our study which is comparable with other study reports and signifies the safety profile of autologous PRP intra-articular injections. 1,3,4 In our study we have found that low grade OA knee (KL grade 1, 2, 3) have better outcomes as compared to higher grade OA knee (KL grade 4) as well as younger age group (50-55 years) has lower WOMAC score as compared to higher age group (60-65 years) which is comparable to study done by Franca Vaccaro, Rita Guitaldi et al which concluded that better results were achieved in younger patients with a lower degree of cartilage degeneration. 5 Pre-treatment blood analysis of our patients showed an average platelet count of 263.48×10 3 /µl.…”
Section: Discussionmentioning
confidence: 99%